The motivation of flaming perpetrators as cyberbullying behavior in social media - Melisa Arisanty; Gunawan Wiradharma (Universitas Padjadjaran, 2022)
The most troubling behavior of cyberbullying is flaming on social media. Technological sophistication makes it easy for everyone to create fake accounts for negative comments to bullying activities on social media. The impact is very detrimental, especially for victims or targets. The most frequent consequences are deep trauma, fear, anxiety, lack of confidence, mental illness, and depression, and they can even motivate the victim to commit suicide. This impact is considered quite dangerous for the victim. Therefore, concrete handling and solutions are needed that can be implemented according to the motivation of the perpetrators to do hate speech and cyberbullying. This study aimed to identify the motives of flaming perpetrators through social media and formulate strategic and practical recommendations for preventing flaming behavior. By identifying through a qualitative approach, phenomenological research strategies, and in-depth interviews with 10 (ten) research informants, the research aims to obtain a comprehensive picture of the motivations of flaming actors in social media. The results of this study indicate some of the motivations of flaming actors in social media, namely excessive fanaticism, personal interests, spontaneous emotions and anxiety, low digital literacy, the anonymity of netizens on social media through second accounts, and lack of empathy. The motivations found in this study are the basis for formulating strategic and practical recommendations in preventing flaming behavior in social media through the KIFE Model (Collaboration, Innovation, News Framing, and Peer group Education). It is practical and effective for Media Literacy and Healthy Digital.